Phosphatidylethanolamine binding protein-4 (PEBP4) is increased in IgA nephropathy and is associated with IgA-positive B-cells in affected kidneys - Taylor, Scott; Pieri, Kyriaki; Nanni, Paolo; Tica, Jure; Barratt, Jonathan; Didangelos, Athanasios (Journal of autoimmunity, 2019)
IgA nephropathy (IgAN) is the most common glomerulonephritis worldwide and a major cause of chronic kidney disease and failure. IgAN is driven by an autoimmune reaction against galactose-deficient IgA1 that results in the generation of autoantibodies and large IgG-IgA immune complexes. Immune complexes accumulate in the glomerular mesangium causing chronic inflammation and renal scarring. A significant proportion of IgAN patients develop end-stage kidney disease and require dialysis or transplantation. Currently, there are no approved specific therapies that can ameliorate the systemic autoimmune reaction in IgAN and no biomarkers that can predict renal inflammation and scarring. In this study, we used shotgun LC-MS/MS proteomics to compare small volumes of urine from healthy subjects and IgAN patients. We identified multiple urine proteins with unknown renal or IgAN function. Our attention was captured by the increase of phosphatidylethanolamine binding protein-4 (PEBP4) in IgAN urine. The function of PEBP4 in IgAN or renal disease is unknown. Increased levels of urine and serum PEBP4 were subsequently validated in different cohorts of IgAN patients and PEBP4 was linked to declining kidney function in IgAN. Strong PEBP4 staining was sporadically seen in IgAN kidney biopsies, colocalising with IgA in glomeruli and in the lumen of kidney tubules. In a small number of IgAN biopsies, PEBP4 colocalised with IgA and CD19 while the increased excretion of PEBP4 in IgAN urine was accompanied by increased excretion of classic B-cell factors BAFF, BCMA and TACI as well as IgA and IgG. PEBP4 is a new IgAN-related protein with unknown function and a likely renal disease marker in urine and serum. •Urine shotgun LC-MS/MS proteomics identified multiple proteins with unknown function in IgA Nephropathy (IgAN).•One of the new IgAN proteins was PEBP4 (Phosphatidylethanolamine binding protein-4).•PEBP4 was increased in IgAN urine and serum and correlated with declining kidney function.•The increase in PEBP4 was likely associated with IgA+/CD19+ B-cells as well as with BAFF, TACI, BCMA, IgA and IgG in urine.